Medical and social domains of ageing research in Singapore (2008–2018): a scoping review - Chen Hee Tam; Elaine Qiao Ying Ho; Sumali Subhashini Hewage; Shilpa Tyagi; Gerald Choon Huat Koh (Singapore Medical Journal)
Introduction: This scoping review examined the number, types and characteristics of journal publications on ageing in Singapore from 2008 to 2018 to determine how ageing research in medical and social domains in Singapore has transformed over time. Methods: Using relevant search terms, articles were extracted from multiple databases and then screened and reviewed for eligibility and inclusion by independent reviewers. Data such as article title, authors, year of publication, name of journal, type of journal, study design and the kind of data used were charted from the included articles for evidence synthesis. Results: Since 2008, there has been a steady increase in the number of publications on ageing in medical and social domains in Singapore. In the medical domain, publications on Ophthalmology (22%) made up the largest proportion of the existing medical literature on ageing in Singapore, followed by Physical Functioning (17%), which involved physiological measurements of physical well-being, and Geriatrics (16%). Non-medical publications comprised 38% of all the included publications, with publications on the social aspects of ageing (43%) forming the largest group in this cluster, followed by publications on Prevention (19%) and Healthcare services (18%). The study design was mostly observational (82%), with only 3% of interventional studies. Conclusion: While ageing research had expanded in Singapore in the last decade, it was predominantly discipline specific and observational in design. As ageing issues are complex, with biology intersecting with psychology and sociology, we call for greater interdisciplinary collaboration, the conduct of more interventional studies, as well as more research in understudied and emerging areas.